ANALYSIS OF THE CONSEQUENCES OF THE 1988 GENEVA CONFERENCE ON AFGHANISTAN'S POLITICAL CRISIS - Wafiullah Aminzai; Gulrahman Mushfiq; Hikmatullah Sayel (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The 1988 Geneva Conference marked a pivotal moment in Afghanistan's protracted political crisis, serving as a diplomatic effort to address the Soviet-Afghan War and its aftermath. This study critically analyzes the consequences of the conference, focusing on its impact on Afghanistan's political landscape, regional stability, and the broader Cold War dynamics. By examining the accords signed between the USSR, the USA, Pakistan, and Afghanistan, the paper explores how the conference aimed to facilitate Soviet withdrawal while attempting to lay the groundwork for peace. However, it also highlights the unintended consequences, including the escalation of internal conflict, the rise of militant factions, and the failure to establish a sustainable political framework. Drawing on primary sources and historical accounts, this analysis underscores the conference's role in shaping Afghanistan's trajectory toward prolonged instability and its implications for global geopolitics. The findings reveal the complexities of international diplomacy in conflict resolution and the enduring challenges of post-war state-building in fractured societies.